Calculus 10th Edition

Published by Brooks Cole
ISBN 10: 1-28505-709-0
ISBN 13: 978-1-28505-709-5

Chapter 2 - Differentiation - Section Project - Optical Illusions: a



Work Step by Step

$\dfrac{d}{dx}(x^2)+\dfrac{d}{dx}(y^2)=\dfrac{d}{dx}(C^2)\rightarrow$ $2x+\dfrac{dy}{dx}(2y)=0\rightarrow\dfrac{dy}{dx}=-\dfrac{x}{y}.$ When $ x=3 $ and $y=4 \rightarrow\dfrac{dy}{dx}=-\dfrac{3}{4}.$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.